Pro-BNP Levels and Its Prognostic Role in Chronic Hypertensive Pregnancies: A Prospective Case-Control Study From A Tertiary Care Hospital - Mehmet Akif Erdol; Atakan Tanacan; Hasan Eroglu; Nazan Vanli Tonyali; Mehmet Erdogan; Aykan Yucel; Nuray Yazihan; Dilek Sahin (Taylor & Francis Group, 2021)
Background: This study aimed to investigate the prognostic value of N-terminal B-type natriuretic peptide (NT-proBNP) in pregnancies with isolated chronic hypertension (HT). Method: 34 pregnant women with chronic HT and 40normotensive controls were enrolled. The association between plasma NT-proBNP levels obtained in the first trimester and perinatal complications were evaluated. Results: NT-proBNP levelsstrongly predicted low birth weight (AUC=0.842, p<0.001). NT-proBNP and birth weight were negatively correlated (r= -0.323, p=0.005). NT-proBNP was found to be an individual determinant of low birth weight in univariate analysis (OR:1.03; 95%CI:1.01-1.04). Conclusion: NT-proBNP levels can be useful to predict low birth weight in pregnancies with chronic HT.